2019
DOI: 10.1002/mabi.201900020
|View full text |Cite
|
Sign up to set email alerts
|

Precisely Controlled Delivery of Abaloparatide through Injectable Hydrogel to Promote Bone Regeneration

Abstract: Side‐effects from allograft, limited bone stock, and site morbidity from autograft are the major challenges to traditional bone defect treatments. With the advance of tissue engineering, hydrogel injection therapy is introduced as an alternative treatment. Therapeutic drugs and growth factors can be carried by hydrogels and delivered to patients. Abaloparatide, as an analog of human recombinant parathyroid hormone protein (PTHrp) and an alternative to teriparatide, has been considered as a drug for treating po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 33 publications
(44 reference statements)
1
21
0
Order By: Relevance
“…SEM indicated that GelMA and GA/GelMA are porous, which contributes to osteogenesis. Ning et al (Ning et al, 2019) reported that injectable photo-crosslinked GelMA hydrogel promoted the healing of bone defects in rats. However, pure GelMA hydrogel is difficult to greatly promote bone regeneration in the absence of any bioactive agent or pretreatment (mineralization in vitro), limiting its application in bone repairing (Zheng et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…SEM indicated that GelMA and GA/GelMA are porous, which contributes to osteogenesis. Ning et al (Ning et al, 2019) reported that injectable photo-crosslinked GelMA hydrogel promoted the healing of bone defects in rats. However, pure GelMA hydrogel is difficult to greatly promote bone regeneration in the absence of any bioactive agent or pretreatment (mineralization in vitro), limiting its application in bone repairing (Zheng et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…SEM indicated that GelMA and GA/GelMA are porous, which contributes to osteogenesis. Ning et al (Ning et al, 2019) reported that injectable photo-crosslinked GelMA hydrogel promoted the healing of bone defects in rats. We designed a GA-delivered GelMA hydrogel, which was used in a mouse femoral fracture model, and the results of micro-CT and histological evaluation indicated that it had a superior effect on bone-fracture healing.…”
Section: Discussionmentioning
confidence: 99%
“…Covalent conjugation/ physical absorption [ 167,168] TRSAW (PTHrP107-111) -Covalent conjugation [ 169] RKVRGPPVSCIKRDSPIQ (LP2) -Covalent conjugation/ physical absorption [ 170] DGEA…”
Section: Angiogenesismentioning
confidence: 99%